A faunistic study of the family Elateridae in Bačka, Serbia - Toscano, Bruno; Štrbac, Pero; Popović, Zorica; Kostić, Miroslav; Kostić, Igor; Konjević, Aleksandra; Krnjajić, Slobodan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
A faunistic study of the family Elateridae was carried out in Bačka, the north-western district of Vojvodina Province in Serbia, focusing on their preferred habitats and soil types. The survey included four locations with a total of 1059 ha, in which 35 species, belonging to 15 genera of Elateridae, were observed. The frequency of larval and adult forms was 58.94% and 67.40%, respectively, proving that wireworms are regular residents of the area. Regarding habitat preferences, it was shown that a majority of Elateridae species prefer open biotopes and wheat crop, while marsh soil, chernozem and alluvium were the preferred soil types of wireworms.